LAW ENFORCEMENT IN THE JUDICIAL POWER FOR JUSTICE - Sobandi Sobandi (Jurnal Pembaharuan Hukum, 2022)
The implementation of the limitation of judicial power in the competence of the commercial court to realize an independent judicial power is normatively spread out in various laws. The purpose of this research is to find out about the implementation of an independent and impartial judicial power or the independence of judicial power is something that absolutely must exist because it is a prerequisite for the realization of the ideals of the rule of law and is a guarantee for the rule of law and justice. the approach method uses a normative juridical approach. The results of the research obtained state that an independent judicial power is one of the pillars for a country based on a democratic system and a state of law. Judicial power that is free and impartial is not only meant to be free from the influence of executive power, but also free from interference in carrying out its duties. Judicial power is an important instrument to guarantee human rights and maintain justice which is a very important element in democracy. If the judicial power in a country has been co-opted by other powers outside it or has sided with certain parties, it can be ascertained that the country is not democratic. The independence of judicial power refers to independence from interference from other power holders in judicial matters.